Press Conference, Pretoria, South Africa, September 6, 2012 - Gordhan, Pravin; Kim, Jim Yong; Diop, Makhtar (2016)
Pravin Gordhan, South African Finance Minister, summarized the nature of the meetings held with ministers and deputies. Jim Yong Kim, President of the World Bank Group, discusses that gender and equity is critical for sustainable economic development, as are good jobs for youth. He believes that along with the South African government, social inclusion and economic growth, especially in the private sector, are not mutually exclusive. The Bank is focused around this issue, and so the Bank needs to figure out a way to be the most effective organization in ending poverty and boosting prosperity. South Africa needed energy in order for the economy to grow and provide good jobs. The Bank is working with the government on many clean energy projects.